Self-healing zwitterionic sulfobetaine nanocomposite hydrogels with good mechanical properties. Issue 55 (7th October 2019) - Lin, Yinlei; Zeng, Zheng; Li, Yuhao; Sun, Sheng; Liu, Xiaoting; He, Deliu; Li, Guangji
Abstract : The prepared zwitterionic sulfobetaine nanocomposite hydrogels can autonomously repair incisions or cracks at ambient temperature without the need for any stimulus and possess excellent mechanical properties. Abstract : The development of zwitterionic hydrogels possessing both excellent self-healing and mechanical properties is of great significance. Herein, a class of zwitterionic sulfobetaine nanocomposite hydrogels was prepared by UV-initiated copolymerisation of zwitterionic sulfobetaine monomer N, N -dimethyl- N -(3-methacrylamidopropyl)- N -(3-sulfopropyl) ammonium betaine (DMAPMAPS) and 2-hydroxyethyl methacrylate (HEMA) in the presence of exfoliated clay platelets uniformly dispersed in an aqueous medium. The effects of the hydrogel compositions, including the DMAPMAPS/HEMA mass ratio and the amount of clay, on the self-healing behaviors and mechanical properties of the nanocomposite hydrogels were investigated. The results indicate that the fabricated zwitterionic sulfobetaine nanocomposite hydrogels can autonomously repair incisions or cracks at ambient temperature without the need for any stimulus and possess excellent mechanical properties.